Urban thermal comfort: study case of the Floresta district of city of Belo Horizonte, MG - Mendonça, Roxane Sidney Resende de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The study of urban thermal comfort enables the effects of human occupation on local climate to be evaluated. The urban environment may obstruct wind paths, causing changes in the temperature and phenomena such as heat island and thermal inversion. Such changes may lead to health problems, increase in energy consumption as well as social and material damages that result from changes in local climate. This paper aims to contribute to the development of an urban planning methodology concerned with both the environment and the human comfort, and also contribute to the preservation of thermal comfort conditions of the Floresta district in the city of Belo Horizonte, MG. Local characteristics were identified and documented in maps, defining homogenous areas that were used as a basis for formulating a hypothesis of local urban ventilation. Data concerning temperature, humidity and winds, collected in the field, were also plotted in maps, after the application of a thermal comfort index. As a result, a synthesis map was produced, pointing to areas that need changes in their development in order to soften the occupation impact on local climate.